(3eNJUQ GdNQbis - (3YeQ Hf GdMSjf Hf YHO Gddg GdNQbj, CHh GdbGSe,J (B334 (3g` s
(3ChdgG (B:s
(3HGH GdWgGQI HGH eG Jchf Hg GdWgGQI ef GdeGA hGdWgGQI HGdeGA GdWGgQ GdeWdb s
(3BNQgG (B:s
(3hEf bJdJ Ce GdhdO SjOgG aYdjgG bjeI faSgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B44 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1626s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs